2004
DOI: 10.1097/00002820-200403000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fatigue in and Care Needs of Turkish Women With Breast Cancer

Abstract: Using Piper's Integrated Fatigue Model, this research project was planned to determine the level of fatigue experienced by Turkish women with breast cancer undergoing adjuvant chemotherapy, to discover the factors affecting fatigue, and to provide a reference by means of which an effective nursing care for such patients could be planned. In assessing the level of fatigue and factors affecting it, a patient information form, the Piper Fatigue Scale, and the Rotterdam Symptom Checklist were used. The reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 14 publications
0
44
0
15
Order By: Relevance
“…Higher scores indicate more fatigue. A validity and reliability study of the PFS for Turkey was carried out by Can et al. (2004), and the Cronbach’s alpha for the entire 22‐item scale was 0·97.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate more fatigue. A validity and reliability study of the PFS for Turkey was carried out by Can et al. (2004), and the Cronbach’s alpha for the entire 22‐item scale was 0·97.…”
Section: Methodsmentioning
confidence: 99%
“…In this longitudinal survey demographic variables and factors associated with the tumour and anti-cancer treatment were unrelated to the fatigue. A large body of evidence exists to support the finding that CRF during anti-cancer treatment is not associated with tumour stage (12,22,23,46,51,56,60,(68)(69)(70) or any demographic (12,22,23,34,49,55,56,60,62,64,(66)(67)(68)(69)(70)(71) or treatment-related variables (12,22,23,46,51,53,55,60,64,(68)(69)(70)(71)(72). In contrast, two studies have reported that females experience more fatigue then males (62,73), three have demonstrated an association between increasing age and lower fatigue (12,34,53), one between marital status and fatigue, with divorced women experiencing the most fatigue …”
Section: Fatigue During Anti-cancer Treatmentmentioning
confidence: 99%
“…In addition to these, therapies cause several adverse effects, the most common ones were loss of energy, fatigue, pain, nausea and vomiting, hormonal changes, and sleep disorders; all of these adverse effects impair daily life functions of patients (102,103). Physical symptoms, fatigue in particular, were reported to have a huge impact on quality of life, which gave rise to the formation of physiologic and psychological symptoms (104).…”
Section: Psychosocial Problems In Patients With Breast Cancermentioning
confidence: 99%